Anxiety Effect on Communication Skills in Nursing Supervisors: An Observational Study - Colomer Sánchez, Ana; Ayuso Murillo, Diego; Lendínez Mesa, Alejandro; Ruiz Núñez, Carlos; Fontán Vinagre, Guadalupe; Herrera Peco, Ivan (My University, 2021)
Communication represents an essential skill in nurse managers¿ performance of everyday activities to ensure a good coordination of the team, since it focuses on the transmission of information in an understandable way. At the same time, anxiety is an emotion that can be caused by demanding and stressful work environments, such as those of nurse managers. The aim of the present study was to analyze the impact of anxiety management on nurse managers¿ communication skills. The sample comprised 90 nursing supervisors from hospitals in Madrid, Spain; 77.8% were women, and 22.2% were men, with an average of 10.9 years of experience as nursing supervisors. The instruments used for analysis were the Sixteen Personality Factor Questionnaire: version five (16PF5) and State Trait Anxiety Inventory (STAI) questionnaires, validated for the Spanish population. The results showed that emotional stability was negatively affected by anxiety (r = ¿¿0.43; p = 0.001), while apprehension was positively affected (r = 0.382; p = 0.000). Nursing supervisors, as managers, were found to possess a series of personality factors and skills to manage stress and communication situations that prevent them from being influenced by social pressure and the opinion of others. Keywords: anxiety; communication; nursing management; personality traits